Histological examination of the skin and agnor parameters of matrix pili cells in the chinchilla - Yasemin Oznurlu; Ilhami Celik; Emrah Sur; Tugba Ozaydin (Eurasian Journal of Veterinary Sciences)
Aim: In this study, histology of the skin and number and area of the argyrophilic nucleolar organiser regions (AgNORs) of the germinal matrix epithelial cells of the chinchilla were investigated by light microscopic techniques. Materials and Methods: Skin samples were taken from 15 adult healthy chinchilla, fixed in formol saline and immersed in parafine. Tissue sections were stained with Crossman's trichrome, Gordon and Sweet's reticuler fiber, Verhoef's elastic fibre and AgNOR staining methods. The total thickness of epidermis and dermis, hair follicle numbers per square milimetres, and number and area of AgNORs of the germinal matrix epithelial cells were measured. Results: AgNORs were seen as 1-4 black dots which distributed in the nuclei of the germinal matrix cells of the hair follicles. The chinchilla compound hair follicle consisted of one or two primary follicles surrounded by multiple smaller secondary follicles. The ratio of secondary to primary hair follicles (S/P) was 13/1. Conclusion: In further studies on a larger population seasonal differences, determination of number and distribution of hair follicules and AgNOR parameters in the germinal matrix cell should be used as significant criteria for fur quality in selection.